Keadilan Ekonomi dalam Islam: Konsep, Prinsip dan Implementasi - Hana Malika Rahmah Sitorus; Fadila Putri (Jurnal Nuansa : Publikasi Ilmu Manajemen dan Ekonomi Syariah, 2025)
Justice is the realization of correct moral values for an object or individual, and is a fundamental foundation in solving the problem of economic and social inequality contained in the conventional system. The Islamic economic system emerged as an alternative solution to overcome the shortcomings of the system. This study uses a literature study approach to analyze the idea of justice in the framework of Islamic economics, which prioritizes the principles of balance and equality, and aims to build mutual trust and harmony so that all individuals can play an active role in creating common prosperity without prioritizing individual interests over collective interests.